2021
DOI: 10.2147/ndt.s307128
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Emergencies During the Covid-19 Pandemic: A 6-Month Observational Study

Abstract: Background The new SARS-CoV-2 has caused an ongoing pandemic. Health prevention measures to contain the outbreak are profoundly affecting the physical and mental health as well as personal freedom of the population. Aim To evaluate psychiatric emergencies in a 6-month period during the COVID-19 pandemic in 2020 compared to those of the corresponding period of the previous year. Methods This monocentric observational study preliminarily collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 57 publications
6
19
1
1
Order By: Relevance
“…In Italy, one of the rst and more heavily affected European countries by the COVID19 pandemic, a reduction of ED accesses for psychiatric consultation was found, ranging from 50% [21] to 37% in the rst phase of the lockdown period (March 8th-May 4th/ 18 th 2020), and a reduction of 11,2 % during the second phase of the lockdown (18th May to June 30 th , 2020) [22] compared with the same periods in 2019. A study considering a longer period of observation (March 1st -August 31 st , 2020) found a persisting reduction in monthly ED access for psychiatric consultation compared with 2019 [23]. Similar results emerged from a Swedish study reporting data from March 2020 to December 2020 and comparing them with the same period in 2019 and 2018 [20].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In Italy, one of the rst and more heavily affected European countries by the COVID19 pandemic, a reduction of ED accesses for psychiatric consultation was found, ranging from 50% [21] to 37% in the rst phase of the lockdown period (March 8th-May 4th/ 18 th 2020), and a reduction of 11,2 % during the second phase of the lockdown (18th May to June 30 th , 2020) [22] compared with the same periods in 2019. A study considering a longer period of observation (March 1st -August 31 st , 2020) found a persisting reduction in monthly ED access for psychiatric consultation compared with 2019 [23]. Similar results emerged from a Swedish study reporting data from March 2020 to December 2020 and comparing them with the same period in 2019 and 2018 [20].…”
supporting
confidence: 57%
“…To the best of our knowledge, this is the rst study evaluating ED access for psychiatric consultations in Italy before, during, and after the lockdown. Previous studies focused on the impact of the rst lockdown on EDs psychiatric consultations with data from a limited time frame [22,23,26,27], and no study has yet investigated the late phase of the pandemic and the long-term effects of prolonged exposure to the pandemic on psychiatric emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies of psychiatric emergency contacts show that regular out-patient contacts have decreased in all psychiatric patients since the pandemic, as a result of restricted face-to-face regulations, hinting at an non-selective decrease of admission rate for all psychiatric patients. 44 – 46 Finally, our results cannot be generalised to all other mental healthcare settings because of inherent differences in mental health service provision across the globe.…”
Section: Discussionmentioning
confidence: 89%
“…During the first weeks of the pandemic, a significant reduction in accessing emergency rooms [ 30 , 31 , 32 ] and in psychiatric hospitalization rates [ 31 , 33 ] was documented in both the United States and European countries, including Italy. Moreover, a mean decrease of 37% in overall access to healthcare has been reported worldwide, both in outpatient visits and inpatient admissions to different healthcare services [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%